Gastric juice ascorbic acid concentrations in helicobacter pylori (+) and (-) patients - Mustafa GÜLŞEN; Kurtuluş YILMAZ; A. Kemal GÜRBÜZ; Sait BAĞCI; Halis KÖYLÜ; Can UYGURER; Necmettin KARAEREN (Turkish Journal of Gastroenterology, 2020)
-